Catolicismo e devoção nos primeiros livros de Física em português, 1615-1645 - Castel-Branco, Nuno (Lusitania sacra, 2024)
In 1590, the Society of Jesus started a mathematics course in Lisbon where subjects now associated with physics and astronomy were taught. In this famous course, many teachers were Jesuits trained outside the country who then went on to their missions in the East. For this reason, historians have associated this academy of mathematics with the new scientific ideas in the Portuguese empire. But in this article, I show that this course also had a huge impact in continental Portugal. In short, it was at the origin of the first books of physics written in Portuguese, where new ideas such as the vacuum, the heliocentric model, and animal mechanics were taught quite early. Through a close reading of manuscripts, this paper also suggests that the Portuguese religious context was one of the driving forces of science in Portugal, due to a type of material piety where encounters with the divine happened through the most material things, including new technologies.